2021
DOI: 10.1038/s41372-021-01142-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of late surfactant preparations: a retrospective study

Abstract: Characterize the use, efficacy, and safety of poractant alfa and calfactant surfactants compared to beractant in preterm infants receiving late surfactant. STUDY DESIGN: We included infants <37 weeks gestational age (GA) discharged from Pediatrix Medical Group-managed neonatal intensive care units . Efficacy and safety outcomes of interest were analyzed. RESULTS: Of 184,770 infants administered surfactant at any time, 7846 (4.23%) received late surfactant at a median (25th, 75th percentile) PNA of 8 days (3, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous systematic evaluations of randomized controlled trials and real-world evidence have shown comparable outcomes for beractant and other commonly used animal-derived surfactants [4,[32][33][34], although these studies did not examine outcomes by the method of administration (e.g., LISA vs INSURE or standard of care). A recent systematic review and meta-analysis of randomized controlled trials (RCTs), published in 2020, demonstrated beractant and poractant alfa treatment as having comparable rates of death, BPD, pneumothorax, and air leak syndrome [4].…”
Section: Review Beractant Treatment For Rdsmentioning
confidence: 99%
“…Previous systematic evaluations of randomized controlled trials and real-world evidence have shown comparable outcomes for beractant and other commonly used animal-derived surfactants [4,[32][33][34], although these studies did not examine outcomes by the method of administration (e.g., LISA vs INSURE or standard of care). A recent systematic review and meta-analysis of randomized controlled trials (RCTs), published in 2020, demonstrated beractant and poractant alfa treatment as having comparable rates of death, BPD, pneumothorax, and air leak syndrome [4].…”
Section: Review Beractant Treatment For Rdsmentioning
confidence: 99%
“…Surfactant dysfunction could play a role in ventilated preterm infants beyond the classic respiratory distress syndrome (RDS), with temporary improvement in pulmonary function seen after surfactant administration in preterm infants requiring prolonged mechanical ventilation 16 17. The use of late surfactant has been increasing over the last decades, with a recent multicentre study reporting that up to 1.4% of preterm infants received surfactant beyond 48–72 hours of age 18. However, the effects of this therapy on short and long-term neonatal outcomes in this population have not been systematically reviewed, and given the lack of effective treatments for evolving BPD in this population, this is a field that needs further investigation.…”
Section: Introductionmentioning
confidence: 99%